EFFICIENT AND FAST INFORMATION GATHERING IN SENSOR NETWORK ORGANISED AS A TREE - N, Pavitha (International Journal of Research -GRANTHAALAYAH, 2014)
In a network organised as a tree how fast the data can be collected is a fundamental objective of this paper. To address this, a number of different techniques are explored and evaluated using realistic simulation models under the many-to-one communication paradigm known as converge cast. Use of TDMA scheduling gives better performance in case of many to one communication. Channel assignment methods such as BFS time slot assignment, Local time slot assignment and multichannel scheduling algorithm Joint Frequency time slot scheduling for moderate size networks of about 100 nodes, by using multiple frequencies are implemented. Performance of these algorithms is evaluated using JProwler simulator. The data rate for each of these algorithms is calculated using simulation. For moderate size networks of about 100 nodes, the use of multi-frequency scheduling can suffice to eliminate most of the interference.